The Role of Lower Crustal Rheology in Lithospheric Delamination During Orogeny - Chen, Lin (Frontiers in Earth Science, 2021)
The continental lower crust is an important composition- and strength-jump layer in the lithosphere. Laboratory studies show its strength varies greatly due to a wide variety of composition. How the lower crust rheology influences the collisional orogeny remains poorly understood. Here I investigate the role of the lower crust rheology in the evolution of an orogen subject to horizontal shortening using 2D numerical models. A range of lower crustal flow laws from laboratory studies are tested to examine their effects on the styles of the accommodation of convergence. Three distinct styles are observed: 1) downwelling and subsequent delamination of orogen lithosphere mantle as a coherent slab; 2) localized thickening of orogen lithosphere; and 3) underthrusting of peripheral strong lithospheres below the orogen. Delamination occurs only if the orogen lower crust rheology is represented by the weak end-member of flow laws. The delamination is followed by partial melting of the lower crust and punctuated surface uplift confined to the orogen central region. For a moderately or extremely strong orogen lower crust, topography highs only develop on both sides of the orogen. In the Tibetan plateau, the crust has been doubly thickened but the underlying mantle lithosphere is highly heterogeneous. I suggest that the subvertical high-velocity mantle structures, as observed in southern and western Tibet, may exemplify localized delamination of the mantle lithosphere due to rheological weakening of the Tibetan lower crust.